An Indirect-Evolution Approach to Newcomb's Problem - Max Albert; Ronald Asher Heiner (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2001)
Players from two populations, predictors and predictees, are randomly matched in a game–theoretic version of Newcomb's Problem. Predictors are able to predict the predictees' choices by observing their type. There are two types of predictees, those who take their predictability into account by using the Backtracking Principle when calculating expected utilities, and those who ignore their predictability by using the Disconnection Principle. Backtrackers are one–boxers, the others are two–boxers. Given predictability, evolution favors the Backtracking Principle. An explicit causal analysis proves that this result does not rest on unusual causal assumptions. – – Das Paper präsentiert eine spieltheoretische Analyse des Newcomb-Problems. Hierbei geht es darum, daß ein Spieler den Zug des anderen voraussagen muß. Die beiden Spieler kommen zufällig zusammen; die Vorhersage bezieht sich auf den Typ des Gegners. Es werden zwei Arten von vorhersagenden Spielern miteinander verglichen. Die eine Art berücksichtigt die Vorhersage bei der Kalkulation des erwarteten Nutzens (Backtracking Principle), die andere ignoriert die Vorhersage dabei (Disconnection Principle). Die "Backtracker" ziehen die "Ein-Schachtel-Lösung" vor, die anderen entscheiden sich für die "Zwei-Schachtel-Lösung". Wenn es Vorhersagefähigkeit gibt, dann wird die Evolution das Backtracking-Prinzip bevorzugen. Eine ausdrückliche kausale Analyse beweist, daß dieses Ergebnis nicht auf unüblichen kausalen Annahmen beruht.
Keywords: D84; C72; 330; Causal Networks; predictions; backtracking; evolution; Evolutionäre Spieltheorie; Rationales Verhalten; Rationale Erwartung; Theorie